Ivermectin-loaded polymeric nanoparticles: Screening the effects of polymers, methods, and the usefulness of mathematical models - Tavares, Eraldo José Madureira; De Araújo, Daniele Ribeiro; Fraceto, Leonardo Fernandes [UNESP] (American Scientific Publishers, 2017)
This research describes the preparation and characterization of ivermectin-loaded polymeric nanoparticles for topical usage, and verifies the effects of different polymers and methods of preparation. This work also evaluates the in vitro release kinetics of selected formulations, and shows the results of an initial investigation about the applicability of several mathematical models to treat the release in Franz cells simulating the release in skin when using nanoparticles. The nanoparticles were characterized with respect to association rate, size, zeta potential and pH. The formulations (12) presented adequate stability and rate of association of about 100%. Some advantages were found for PLA nanocapsules prepared by nanoprecipitation. These nanoparticles measured only about 180 nm and presented good stability results: relatively constant in size, zeta potentials usually below -30 mV, polydispersity index below 0.2, and mild pH changes with time. The analysis of mathematical models supported the use of: Higuchi's equation for monolayer and multilayer of skin; WI Higuchi's time1/2kinetics; diffusion from spheres and capsules; and zero order. However, some concerns are highlighted about the use of Korsmeyer-Peppas's generalized equation and dissolution models. The combined utilization of several models could provide reasonable predictions that could help elucidate the release mechanisms and decrease the necessity of a trial-and-error approach, saving time and cost. The ability of in vitro assays to simulate the destabilization behavior of nanoparticles should be verified. The systems being investigated here could be useful to releases of the drug from follicles and the first layers of stratum corneum, where the nanoparticles would form reservoirs for longer releases. This research will be helpful to combine polymers and methods of preparation for developing improved nanoparticle formulations for several uses.
Keywords: Controlled release/delivery; Formulation; In vitro models; Mathematical model; Nanocapsules; Nanospheres; Nanotechnology; Poly(lactic/glycolic) acid (PLGA, PLA); Polymeric drug delivery systems; Polymeric nanoparticles